2011
DOI: 10.1007/s10494-011-9332-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Co-flowing Subsonic and Sonic Jets

Abstract: Effect of an annular co-flow jet on the center jet at subsonic, correctly expanded and underexpanded sonic conditions was studied experimentally. It is found that the co-flow retards the mixing of the primary jet, leading to potential core elongation. The characteristic decay of the jet is also retarded in the presence of co-flow. With co-flow core length elongation of 40% and 80% were achieved for correctly expanded and underexpanded (NPR 7) sonic jets, respectively. Shadowgraph pictures show that the co-flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The primary jet potential core length (PCL) is defined as the axial extension until the primary exit nozzle velocity prevails for subsonic jets. 14) Figure 6 plots centerline total pressure variation for lip thickness 0:2D p co-flowing jet, Mach 0.6, for the seven different turbulence models and for the experiment. It is evident that the SA model produces data that agrees well with the experimental data, consistent with its advantage in predicting the flow field characteristics, and the k-¾ standard model decays slower than the experiment in the characteristic decay region.…”
Section: Validation Of Cfd With Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary jet potential core length (PCL) is defined as the axial extension until the primary exit nozzle velocity prevails for subsonic jets. 14) Figure 6 plots centerline total pressure variation for lip thickness 0:2D p co-flowing jet, Mach 0.6, for the seven different turbulence models and for the experiment. It is evident that the SA model produces data that agrees well with the experimental data, consistent with its advantage in predicting the flow field characteristics, and the k-¾ standard model decays slower than the experiment in the characteristic decay region.…”
Section: Validation Of Cfd With Experimental Resultsmentioning
confidence: 99%
“…This is because co-flow protects the main jet from interacting with the atmosphere thereby inhibiting mixing. 14) For lip thicknesses 1.0D p and 1:5D p , core length gets shortened up to 2.8D p and 2:4D p with a percentage reduction of 68 and 72% compared to lip thickness 0:2D p , respectively, due to the formation of the recirculation zone. The effect of lip thickness is well pronounced both in the potential core and characteristic decay region.…”
Section: Axial Pitot Pressure Decaymentioning
confidence: 93%
See 2 more Smart Citations
“…Deo et al [28] investigated experimentally the effect of the initial conditions on the turbulent plane jet. Lovaraju and Rathakrishnan [24] studied experimentally the effect of coflow jet on the centered subsonic and sonic jets and observed that the co-flow is effective in preserving the shock-cell structure of the inner jet. Sandberg et al [29] computed two-dimensional compressible pipe flow into a co-flow with direct numerical simulation and demonstrated self-preserving behavior of turbulence statistics at nozzle exit.…”
Section: Introductionmentioning
confidence: 99%